2000
DOI: 10.1097/00005768-200009000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass increases in less than 4 wk of voluntary exercising in growing rats

Abstract: Daily spontaneous exercise training induced an increase in bone mass and bone volume in less than 4 wk. Further studies are needed to fully investigate these changes during the very first days of exercising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 0 publications
6
27
1
2
Order By: Relevance
“…This difference might have been caused by the difference in the age of the rats. The age of the rat in the exercise and food restriction phase was lower in our study (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks old) than in Dimarco et al's study (17-30 weeks old). Our findings could suggest that young female rats may be sensitive to the negative effects of the interaction of voluntary running exercise and food restriction.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This difference might have been caused by the difference in the age of the rats. The age of the rat in the exercise and food restriction phase was lower in our study (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks old) than in Dimarco et al's study (17-30 weeks old). Our findings could suggest that young female rats may be sensitive to the negative effects of the interaction of voluntary running exercise and food restriction.…”
Section: Discussioncontrasting
confidence: 75%
“…In previous studies, it has been reported that running exercise under ad libitum feeding conditions in female rats induced high bone mass [16] or high BMD [3,17]. However, the influence of running exercise on bone in female rats has not been reported under food restriction conditions.…”
Section: Introductionmentioning
confidence: 95%
“…We have no explanation for the apparent discrepancy, but we note that blood withdrawn during animal sacrifice only represents a snapshot at a single time point and not the sustained activity of osteoblasts and/or osteoclasts throughout the training period. In support, several studies have demonstrated training-induced elevations in BMD in the absence of any alterations in serum biomarkers (7,19). Therefore, we recognize the significant limitation of extrapolating on bone cell activity fi-om a single serum sample taken at one time point.…”
Section: Discussionmentioning
confidence: 95%
“…In both instances, resumption of activity leads to restoration of bone. It is also known that bone mass increases with mechanical stress (Maddalozzo & Snow, 2000;Swezey, Swezey, & Adams, 2000), and that those who engage in aerobic activity have higher bone density than those who do not (Bidoli, Schinella, & Franceschi, 1998;Coupland et al 1999;Holy & Zerath, 2000;Kano, 1998). The relationship between calcium intake and bone is well established (Holm & Walker, 1990;Reid, Ames, Evans, Sharpe, & Gamble, 1994;Soroko, Holbrook, Edelstein, & Barrett-Connor, 1994;Weaver, 2000;Wolf et al, 2000).…”
Section: Physical Activitymentioning
confidence: 99%